A novel approach for pattern recognition by using network and theory of complexity - Babič, Matej (Journal of Production Engineering, 2023)
In this article we present new method for pattern recognition and calculating all closeness centralization of network created with connection maximum value of 3D graph of hardenend specimens. Intelligent systems are a new wave of the embedded and real-time systems that are highly connected, with a massive processing power and performing complex applications. We use a method which combines an intelligent genetic algorithm and multiple regression to predict all closeness centralization of network created with connection maximum value of 3D graph of hardened specimens. With method of intelligent system, genetic programming and multiple regression we increase production of process of laser hardening, because we decrease time of process and increase topographical property of materials.